PERSEPSI WISATAWAN TERHADAP WISATA SPIRITUAL MELUKAT DI TAMAN BEJI SAMUAN, BALI - Ekasani, Kadek Ayu; Ni Made Ayu Natih Widhiarini; Agung Rizky Fedora Febrawan (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
Melukat is a ceremony to purify and cleanse the bad and dirty nature that exists in every human being. Melukat is a Balinese Hindu tradition that has been passed down from generation to generation and is still practiced today. In addition, Melukat is also said to be a "Healing" activity to relieve stress, depression, and emotions, and gain peace of mind. The purpose of this research is to find out tourists' perceptions of melukat spiritual tourism activities in Taman Beji Samuan, both in terms of satisfaction, impressions, and benefits from spiritual values, safety, comfort, and so on. The method used in this research is qualitative. Data collection techniques were carried out with two events, namely participatory observation and interviews with ten tourists who Melukat at Taman Beji Samuan and also two resource persons who are managers at Taman Beji Samuan who have worked for decades in that place. The data analysis technique used is a qualitative descriptive analysis technique, namely the results of interviews and observations collected about tourist perceptions are interpreted as descriptively qualitative. The result of this research is the identification of Tourist Perceptions of Melukat Spiritual Tourism at Beji Samuan Park and providing information for tourists about the procession in Melukat activities so that tourists can understand Melukat activities at Taman Beji Samuan. Tourists' perception of facilities and accessibilities is still lacking because facilities such as places to eat are not widely available, and road access to the location is steep and climbing, making tourists tired. For this reason, more attention is needed from the village government and managers towards these shortcomings so that they can be corrected and increase the number of tourist visits.